XBRL Adoption: An Examination on the Malaysian Business Reporting System (MBRS) - Azleen Ilias; Erlane K Ghani; Nasrudin Baidi; Rahida Abdul Rahman (2020)
In 2018, Small Medium Enterprises (SMEs) that are registered with the Companies Commission of Malaysia (SSM) in Malaysia are required to prepare their annual return using eXensible Business Reporting Language (XBRL) via Malaysian Business Reporting System (MBRS), followed by voluntary submission of financial reports and statements in 2019. This study seeks to explore if practitioners are aware of and fully understand MBRS. This study also investigates the level of MBRS preparation among the companies. In addition, this study examines the practitioners‟ readiness, intention to use and experience in using MBRS. Finally, the factors influencing MBRS adoption among the practitioners will be examined. Using a questionnaire survey as the research instrument, the data shows that there are improvements to be made in regards to the understanding, readiness and intention to use the MBRS which is requirement by SSM. Additionally, this study shows how optimism, innovativeness, discomfort and insecurity influence the intention to use MBRS in the future. The finding indicate that an XBRL adoption via MBRS received a more positive response from the practitioners and hence, signals a possible successful XBRL adoption in Malaysia. This in turn, ensures the stakeholders a high quality financial reporting.